First trimester screening of circulating C19MC microRNAs can predict subsequent onset of gestational hypertension - Hromadnikova, Ilona; Kotlabova, Katerina; Hympanova, Lucie; Doucha, Jindrich; Krofta, Ladislav (PloS one, 2014)
OBJECTIVE: The objective of the study was to evaluate risk assessment for gestational hypertension based on the profile of circulating placental specific C19MC microRNAs in early pregnancy. STUDY DESIGN: The prospective longitudinal cohort study of women enrolled at first trimester screening at 10 to 13 weeks was carried out (n = 267). Relative quantification of placental specific C19MC microRNAs (miR-516-5p, miR-517*, miR-518b, miR-520a*, miR-520h, miR-525 and miR-526a) was determined in 28 normal pregnancies and 18 pregnancies which developed gestational hypertension using real-time PCR and a comparative Ct method relative to synthetic C. elegans microRNA (cel-miR-39). RESULTS: Increased extracellular C19MC microRNA plasmatic levels (miR-516-5p, p<0.001; miR-517*, p = 0.007; miR-520h, p<0.001; miR-518b, p = 0.002) were detected in patients destined to develop gestational hypertension. MiR-520h had the best predictive performance with a PPV of 84.6% at a 7.1% false positive rate. The combination of miR-520h and miR-518b was able to predict 82.6% of women at the same false positive rate. The overall predictive capacity of single miR-518b (73.3% at 14.3% FPR), miR-516-5p (70.6% at 17.9% FPR) and miR-517* (57.9% at 28.6% FPR) biomarkers was lower. CONCLUSION: The study brought interesting finding that the up-regulation of miR-516-5p, miR-517*, miR-520h and miR-518b is associated with a risk of later development of gestational hypertension. First trimester screening of extracellular miR-520h alone or in combination with miR-518b identified a significant proportion of women with subsequent gestational hypertension.
Keywords: hypertenze indukovaná těhotenstvím; lidské chromozomy, pár 19; první trimestr těhotenství; Caenorhabditis elegans; sekvence nukleotidů; MicroRNAs; Chromosomes, Human, Pair 19; mikro RNA; Pregnancy; těhotenství; Placenta; Hypertension, Pregnancy-Induced; Prospective Studies; placenta; Animals; lidé; ženské pohlaví; Humans; zvířata; Base Sequence; Female; Pregnancy Trimester, First; prospektivní studie